Kecakapan Pendidik dalam Menggunakan Media Pembelajaran Online di Masa Pandemi - Fiaz Ulil Hibar An-Nashr Fiaz Ulil Hibar An-Nashr; Firdan Edwin Harliansyah Firdan Edwin Harliansyah; Fery Diantoro Fery Diantoro (STAI Attanwir Bojonegoro, 2021)
The pandemic that has occurred throughout the world due to the spread of the COVID-19 outbreak is indeed very disturbing and has an effect on vital sectors. One of the wichs is the education sector. From this, the components in education (curriculum) become more flexible in their application, which must be followed by educators as the subject of delivering knowledge so they can be well accepted by students (objects) without reducing their enthusiasm for learning at the pandemic era. Run face-to-face and must switch to online learning. Therefore, educators need to master online learning media which badly need in the situation of the COVID-19 pandemic. However, there are still educators who are not ready to face online learning, especially in the operation of learning media. The role of schools, in this case, is also important, for the sake of smooth and successful online logging in the current pandemic era, schools must provide training and guidance to existing educator members because not all are competent in terms of operating online learning media. So that educators can adjust beforehand for teaching readiness in the current pandemic situation. Motivational touch is also the crucial thing, to foster a sense of enthusiasm and overcome the psychology of students in undergoing online learning because there is less good readiness and is something new that is felt by educators and students. This research aims to understand how competent and readiness of education is in using learning media during the pandemic era in online learning. the method used in its preparation, using quantitative methods, namely. pandemi yang terjadi diseluruh dunia akibat dari menyebarnya wabah COVID-19 memang sangat meresahkan, sehingga berefek kepada sektor-sektor yang sangat vital, salah satunya sektor pendidikan. Dari hal itu, maka komponen-komponen dalam pendidikan (kurikulum) menjadi lebih fleksibel dalam penerapannya yang harus dikuti oleh pendidik sebagei subjek penyampaian ilmu pengetauhan, agar dapat diterima secara baik pula oleh peserta didik (objek) tanpa mengurangi semangat belajar dimasa pandemi yang sukar rasanya dijalankan secara tatap muka dan harus beralih ke pembelajaran online. Maka, sangatlah penting bagi pendidik untuk menguasai media pembelajaran online yang sangat diperlukan dalam sitausi pandemi COVID-19. Namun, pada kenyataanya masih ada pendidik yang belum siap menghadapi pembelajaran online, apalagi dalam pengoprasian media pembelajarannya. Peranan sekolah dalam hal ini juga sangat vital, demi kelancaran dan menyukseskaan pembalajan online di era pandemi seperti sekarang ini, sekolah harus mengadakan pelatihan dan bimbingan kepada anggota pendidik yang ada, karena tidak semua cakap dalam hal pengoprasian media pembelajaran online. Agar pendidik mampu menyesuaikan terlebih dahul demi kesiapan mengajar dalam situasi pandemi sekarang ini. Sentuhan motivasi juga sangat penting, demi menumbuhkan rasa semangat dan mengatasi psikologi peserta didik dalam menjalani pembelajaran online, karena belum adanya kesiapan yang baik dan merupakan hal baru yang dirasakan pendidik dan peserta didik. Tujuan dari penelitian ini adalah meraba seberapa cakap dan keseiapan pendidikan dalam menggunakan media pembelajaran dimasa pandemi dalam pembelajaran online. Metode yang digunakan adalah metode kuantitatif, yaitu